Influência do volume reduzido e do estádio fenológico da planta de soja no controle da Anticarsia gemmatalis (Hübner, 1818) - Brenha, Jeruska Azevedo Moreira [UNESP] (2015)
The reduction in spray volume is a trend in agriculture, since it is intended to decrease costs while operational capacity is increased. However, if adjusted to the target location in plant, the control of pest problems will have better results. Thus the aim of this work was to evaluate the influence of the application of reduced volumes at different growth stages of soybean plants to control Anticarsia gemmatalis (Hübner, 1818). The design was a randomized block with 12 treatments plus control, with 4 replications. The treatments were in a factorial (2 times of applications and R5.2x3 sprayer volumes 70, 105 and 140 L ha-1 x 2 insecticides sprays and pesticide + mineral oil). The spray deposit ratings were made, covering of the plants after the spray droplet spectrum , surface tension , productivity and mortality of caterpillar. Considering the results of this study, it is concluded that the influence of reduced volume did not change the application's parameters at different times of application, for A. gemmatalis control, pointing out that there is technical feasibility in the use of reduced spray volume (70 L.ha- 1)